Limited effectiveness of patent blue dye in addition to isotope scanning for identification of sentinel lymph nodes: Cross-sectional real-life study in 1024 breast cancer patients. (September 2016) - Rauch, Philippe; Merlin, Jean-Louis; Leufflen, Lea; Salleron, Julia; Harlé, Alexandre; Olivier, Pierre; Marchal, Frédéric
Abstract: Background: Although morbidity is reduced when sentinel lymph node (SLN) biopsy is performed with dual isotopic and blue dye identification, the effectiveness of adding blue dye to radioisotope remains debated because side effects including anaphylactic reactions. Patients and Methods: Using data from a prospectively maintained database, 1884 lymph node-negative breast cancer patients who underwent partial mastectomy with SLN mapping by a dual-tracer using patent blue dye (PBD) and radioisotope were retrospectively studied between January 2000 and July 2013. Patients with tumors <3 cm and with >1 node detected by one of the two techniques (N = 1024) were included in this real-life cross-sectional study. Results: Among the 1024 patients, 274 had positive SLN detected by isotopic and/or PBD staining. Only 4 patients having no detectable radioactivity in the axilla had SLN identified only by PBD staining (blue-only) while 26 patients had SLN only identified by isotopic detection (hot-only) illustrating failure rates of 9.5% (26/274) and 1.5% (4/274), respectively. Among these four patients, two had negative lymphoscintigraphy. Therefore, the contribution of PBD to metastatic nodes identification was relevant for only 2/274 patients (0.8%). Three patients (0.3%) had an allergic reaction with PBD, and anaphylactic shock occurred in two cases (0.2%). Conclusions: The added-value of PBD to reduce the false-negative rate of SLN mapping is only limited to the rare cases in which no radioactivity is detectable in the axilla (<1%). When a radioisotope mapping agent is available, the use of PBD should be avoided, because it can induce anaphylaxis. Highlights: Blue dye and radioisotope SLN mapping in 1024 BC pts. Limited blue dye effectiveness. Use of PBD should be avoided when a radioisotope mapping agent is available.